Patients with functional gastrointestinal disorders—importance of communication between physician and patient assessed in a cross-sectional cohort study - Goebel-Stengel, Miriam; Paulsen, Ute; Bennerscheidt, Petra; Zipfel, Stephan; Stengel, Andreas (Frontiers in Psychiatry, 2023)
Functional gastrointestinal disorders are frequent diseases often associated with a pronounced burden reflected in a greatly reduced quality of life. Patients are seeking medical help but may be perceived as demanding and challenging. For successful diagnosis and treatment of these patients, a good doctor-patient communication is key. However, so far, only few studies focus on the physicians’ perspective of the doctor-patient communication. The present study cross-sectionally investigated 520 physicians using the validated difficult doctor-patient relationship questionnaire and the treatment satisfaction questionnaire from the physician’s perspective along with several ad hoc questions. Data from 5,354 physician-patient conversations (one conversation per patient) was included. Physicians participating in this study mostly suspected stress-related burdens as the cause of functional gastrointestinal disorders (65.4%), while patients rather suspected food (55.4%) or other somatic causes (43.6%). The physician-patient relationship was rated just below the threshold for difficult interactions (cut-off ≥30, mean ± SD in the current sample: 28.6 ± 9.6) with 49.1% of physicians reaching a score of ≥30. Although physicians overall felt confident in the doctor-patient communication even in difficult conversations (61.9%), only 33.1% reported to have enough time for these patients and only 5.6% felt sufficiently compensated for discussions with patients with functional gastrointestinal disorders. Therefore, education of physicians on functional gastrointestinal disorders, training of physicians in physician-patient communication as well as an improved reimbursement of speaking medicine should help to further improve care for these patients and also treatment satisfaction on both the side of the patients as well as the physicians.